HOLDING TIME EFFECT OF THE CARBURIZING PROCESS ON FREIGHT TRUCK IMITATION NOZZLE AGAINST CORROSION RATE - Sigit Gunawan (Universitas Muhammadiyah Semarang, 2023)
One of the important components in the diesel engine fuel system is the nozzle. The material for making the nozzle must have a fairly high corrosion resistance. This study aims to determine the effect of the holding time of the imitation truck carburizing nozzle carburizing process on the corrosion rate. The research variable is the carburization holding time. Variation of holding time 90, 120, 150, 180 and 210 minutes. The method used in this study is an experiment through laboratory testing using the carburization process. The carburization process was carried out using coconut shell charcoal carburized media and added barium carbonate. The nozzle is then made into a specimen for hardness test, corrosion test and microstructure test. Specimens were made in two conditions, namely raw material conditions and conditions with carburization treatment. The carburizing process was carried out by heating the test specimens in a clay box filled with a mixture of carburizing media and barium carbonate (BaCO3) at 900ºC with various holding times of 90, 120, 150, 180 and 210 minutes, then the specimens were quenched by dipping. into the cooling medium in the form of oil to room temperature. The next stage is testing hardness, corrosion and microstructure. The results showed that the increase in holding time caused the hardness to increase and the corrosion rate tended to decrease. The highest average hardness is 975.4 VHN at holding time 210 minutes, and the lowest corrosion rate is 1.6328 mm/year at holding time 210 minutes. As the holding time of the carburizing process increased, the C content increased, thus stimulating the formation of martensite and chromium carbides.